2013
DOI: 10.1073/pnas.1302167110
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4,5-bisphosphate alters pharmacological selectivity for epilepsy-causing KCNQ potassium channels

Abstract: Pharmacological augmentation of neuronal KCNQ muscarinic (M) currents by drugs such as retigabine (RTG) represents a first-in-class therapeutic to treat certain hyperexcitatory diseases by dampening neuronal firing. Whereas all five potassium channel subtypes (KCNQ1-KCNQ5) are found in the nervous system, KCNQ2 and KCNQ3 are the primary players that mediate M currents. We investigated the plasticity of subtype selectivity by two M current effective drugs, retigabine and zinc pyrithione (ZnPy). Retigabine is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 48 publications
4
32
0
Order By: Relevance
“…1B). The closing of the KCNQ2 channel in response to decreased PIP 2 concentration is consistent with previous observations (6). The M1 and Dr-VSP experiments support the positive effects of PIP 2 on current amplitude.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…1B). The closing of the KCNQ2 channel in response to decreased PIP 2 concentration is consistent with previous observations (6). The M1 and Dr-VSP experiments support the positive effects of PIP 2 on current amplitude.…”
Section: Resultssupporting
confidence: 80%
“…We first cotransfected KCNQ2 and Musicrinic receptor 1 (M1) in the cells, where PIP 2 is reduced through the phospholipase C (PLC)-mediated lipid hydrolysis (3,14). Consistent with previous reports (6,11,19), we observed that activation of the M1 receptor by Oxo-M (5 μM) induces a dramatic suppression of the current amplitude (Fig. 1A).…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…1B1), similar to neurons in which Mcurrent was suppressed by drugs or genetic manipulations. 94,98,99 Furthermore, the M-current blocker XE991, which increased input resistance and firing frequency, and reduced latency to first AP in control neurons, failed to do so in mutant neurons. In voltage-clamp recordings, M-currents of acutely isolated CA1 pyramidal neurons from BACE1-deficient mice were reduced by 2/3 and displayed faster decay kinetics when compared to their wild type counterparts (Fig.…”
Section: Direct Interaction and Kcnq Gatingmentioning
confidence: 99%